Aprendizagem de conceitos físicos a partir da construção de uma mini geladeira de pastilha Peltier - Moraes, Rafael da Silva (Brasil, 2019)
In an educational scenario composed of many difficulties regarding teaching / learning in the discipline of Physics, the use of innovative methodologies is a tendency to be analyzed to obtain a higher performance in the discipline. Maker culture can be one of those tools that, coupled with education, has a positive effect. The present work aims to describe how the culture maker can help in the process of teaching and learning. We carried out a bibliographical research to understand about this culture, its main aspects and how it can be inserted in the school environment. It was then proposed to build a mini peltier pellet refrigerator from the perspective maker, and at the time of construction and operation of this, identify the main physical concepts that can be developed with the students. The mini refrigerator after built, generated a satisfactory result, reducing the internal temperature by 20.4 ° C. We elaborate some questions about the construction, the functioning and the physical concepts that can be learned. Finally, we conclude that the work can act as a proposal for a rather efficient didactic approach.